Taxonomic revaluation of the Ahaetulla prasina (H. Boie in F. Boie, 1827) complex from Northeast India: resurrection and redescription of Ahaetulla flavescens (Wall, 1910) (Reptilia: Serpentes: Colubridae) - Srikanthan, Achyuthan N.; Adhikari, Omkar Dilip; Kumar Mallik, Ashok; Campbell, Patrick D.; Bhushan Bhatt, Bharat; Shanker, Kartik; Rajagopalan Ganesh, Sumaithangi (European Journal of Taxonomy, 2022)
The taxonomic status of the nominal taxon Dryophis prasinus flavescens Wall, 1910 is reevaluated herein. Based on molecular data generated from fresh collections of Ahaetulla prasina (H. Boie in F. Boie, 1827) auctorum from Northeast India and, additionally, morphological data from museum specimens originating from the same areas, we resurrect this taxon as Ahaetulla flavescens (Wall, 1910) comb. nov. We clarify the status, identity and locations of its type specimens, rediscover, redescribe and illustrate those specimens and also designate a lectotype in order to effect a proper taxonomic redefinition of this nominal taxon. We provide further details on the morphology and diagnosis of this species and elucidate its phylogenetic position. We also provide a summary of the natural history and distribution of this species. Adding to the known cryptic diversity and genetic divergence within Southeast Asian populations, this work also hints at the need for a taxonomic revision of the A. prasina complex. This work complements a previous study on the A. prasina complex focusing on populations in Indonesia. Taken together, these two studies represent phylogenetic reconstructions from different populations of the A. prasina complex across its distribution range, on the Asian mainland and the surrounding islands.